A study of PP/PET composites: Factorial design, mechanical and thermal properties. (December 2016) - Nonato, Renato Carajelescov; Bonse, Baltus Cornelius
Abstract: Due to the economic importance of polypropylene (PP) and polyethylene terephthalate (PET), and the large amount of composites made with PP matrix and recycled PET as reinforcing material; an investigation was performed regarding the mechanical and thermal behavior of PP composites containing recycled polyethylene terephthalate fibers (rPET). Interfacial adhesion between the two materials was achieved by adding a compatibilizer, maleic anhydride grafted polypropylene, PP-g-MA. Mechanical behavior was assessed by tensile, flexural, impact and fatigue tests, and thermal behavior by HDT (Heat Deflection Temperature). Fractured surfaces and fiber were investigated by scanning electron microscopy. Multiple regression statistical analysis was performed to interpret interaction effects of the variables. Tensile strength, tensile modulus, flexural strength, flexural modulus and HDT increased after rPET fiber incorporation while strain at break, impact strength and fatigue life decreased. Addition of compatibilizer increased tensile strength, flexural strength and flexural modulus, fatigue life and HDT while tensile modulus, strain at break and impact strength decreased. However, at low fiber content, the impact strength increased, probably due to nucleation effects on PP.